PERCOBAAN PENGGUNAAN PESTISIDA UNTUK MENCEGAH SERANGAN JAMUR PEWARNA PADA ROTAN - Dominicus Martono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Sapstain fungi are the common fungi attacking fresh cut rattan which cause serious economic deterioration. The pattern of sapstain infestation on fresh cut rattan and its prevention were studied in rattan processing industries at Cirebon.The material used consisted of fresh cut rattan of semambu (Calamus scipionum Burr) and seel (Daemonorop sp), measuring 30 cm long. Five pesticides were tested on rattan for sapstain protection. The staining percentage was inspected fomightly for two months, whereas the pattern of fungal attack was inspected weekly for one month. The data were completely randomised design analysed and tested by Dunnet procedure at level 1% and 5%. The degree of staining defect was transformed into arcsin √%.The result showed that semambu and seel were susceptible to sapstain. The initial infestation starts when the rattan is freshly cut, indicating by the staining on the cutting surface. The fungi mycelia penetrate through parenchym-cell and tenninate in the nodes. The rate of penetration fungi mycelium is approximately 6 cm per week.The TCMTB/MTC, Thiobendazol + IF 1000 and MBT pesticides were found effective to prevent sapstain on fresh cut rattan.